CONSTRUCTING THE MEANING OF LIFE IN LAMPUNG BUBANDUNG THROUGH THE SIGNIFIER–SIGNIFIED RELATIONSHIP: A FERDINAND DE SAUSSURE SEMIOTIC STUDY - Astria Astria; Mei Fatmila Sari; Muhammad Ramdhan Fathin Al Farabi3; Detia Aulia Oktarina (Wiyata Budaya: Jurnal Pendidikan Dalam Konteks Humaniora, 2026)
Bubandung is a form of Lampung oral literature that embodies religious, moral, and cultural values passed down across generations. As an oral literary tradition, Bubandung employs a system of signs to convey philosophical messages about human life, making it a valuable subject for semiotic analysis. This study aims to describe the relationship between the signifier and the signified in Bubandung using Ferdinand de Saussure's semiotic theory and to reveal the meanings constructed through this relationship. This research employed a qualitative approach with a descriptive method. The data source was the text of Bubandung, collected through a literature study. Data were gathered using documentation techniques by conducting intensive readings, identifying linguistic units containing signs, and analyzing them based on the relationship between signifier and signified according to Ferdinand de Saussure's semiotic framework. The findings indicate that each stanza of Bubandung forms an interconnected system of signs representing the journey of human life, the inevitability of death, the importance of maintaining a relationship with God, and the awareness that wealth, social status, and worldly pleasures are temporary. The relationship between signifier and signified constructs a coherent meaning, demonstrating that Bubandung functions not only as entertainment but also as a medium for transmitting the religious, moral, and cultural values of the Lampung community. These findings confirm that Ferdinand de Saussure's semiotic approach effectively reveals the structure of meaning embedded in oral literature as a representation of a community's worldview.